Zr-DLC coatings - analysis of the friction and wear mechanisms - Vitu, Tomas; Pimentel, Bernando Joao Vitor; Escudeiro, A.; Cavaleiro, Albano; Polcar, Tomas (International Conference on Plasma Surface Engineering, 2013)
In the last few decades, the amorphous or nanostructured carbon structures prepared by several deposition techniques are a subject of considerable research interest due to their excellent properties, such as high hardness and chemical inertness, wear resistance or low friction. There have been also attempts to improve the mechanical, chemical or tribological properties of carbon coatings by addition of other elements. Generally, specific chemical composition of the modified films strongly affects the surface energy, and may modify various physical properties and decrease compressive stress, making some metal-doped carbon films suitable for large variety of practical applications. Our work was focused on the structural, chemical and tribological properties of Zr-doped DLC coatings with controlled composition. The main attention was paid to the determination of the wear mechanisms, characterization of the worn surfaces and wear debris and formation of a tribolayer affecting the tribological process. The as-deposited coatings and worn surfaces were studied using 3D optical profilometry, Raman spectroscopy, X-Ray diffraction (XRD) and Scanning electron microscopy (SEM).